Methodological basis for identifying promising industries of business specialization in Russian regions while developing digital technologies - S. L. Ivanov (Вестник университета)
A methodological approach has been developed to identify promising sectors of business specialization in the Russian regions in order to develop speciﬁc types of digital technologies in them. The approach implementation has been evaluated in several stages. At the ﬁrst stage, the leading regions have been identiﬁed in terms of growth rates of indicators characterizing the use of digital technologies in organizations for the period from 2020 to 2022. At the second stage, business specialization industries groups have been revealed in which the digital technologies development is the highest priority. It became possible thanks to the identiﬁcation of “transition” groups of industries by the level of digitalization. The leading regions in terms of the use of digital technologies in organizations depending on the growth rate of the level of their dissemination have been identiﬁed. Priority sectors of business specialization have been revealed by the share of organizations using digital technologies. In particular, it has been found that wholesale and retail trade, as well as the information technology industry have the potential for the spread of technologies for collecting, processing, and analyzing big data. The manufacturing industry, wholesale and retail trade, and information technologies have the potential to spread digital platforms.